EFFECTIVITY IN VITRO OF Averrhoa bilimbi L ETHANOLIC EXTRACT AGAINTS Escherichia coli AND Staphylococcus aureus GROWTH - Erwin Kukuh Widhianto; Ransidelenta Vistaprila Elmarda; Maya Dian Rakhmawatie (Universitas Muhammadiyah Semarang, 2017)
Averrhoa bilimbi L, or in Indonesian named belimbing wuluh has been widely used by the community as a complement to cuisine. From many studies, fruit or leaves of Averrhoa bilimbi L declared to have antibacterial activity. The activity is caused by the antibacterial content in Averrhoa bilimbi L, such as flavonoids, saponins, and tannins. This research is conducted to test the effectiveness of ethanolic extractof Averrhoa bilimbi L as antibacterial. The bacteria used to tested are Gram + Staphylococcus aureus and Gram- Escherichia coli, both of which are pathogenic bacteria in humans. This research was a pure experimental design with posttest only control group design. Averrhoa bilimbi L was extracted using maceration method with 96% ethanol solvent. The thick extract of the Averrhoa bilimbi L was diluted using 2% DMSO solvent to concentration range 0,19%; 0,39%; 0,78%; 1,0%; 1,56%; and 3,12% (v/v).Extracts with various concentrations were then tested to S. aureus and E. coli bacteria, and each concentration was repeated four times. MIC and MBC test were conducted by dilution method using Mueller Hinton Broth and Mueller Hinton Agar. MIC values were minimal concentration of no bacterial test growth , as measured by observing the difference of absorbance before and after incubation oftreatment solution using spectrophotometer λ 625 nm. The MBC values are minimal concentration there is no bacterial colony growth after treatment.The statistical test showed that there was significant difference of absorbance value at each concentration of Averrhoa bilimbi L ethanolic extract test on both bacteria. Based on ANOVA analysis, p value was 0,001. In linear regression analysis, the relationshipbetween extract concentration and the absorbance of S. aureus bacteria, is generated with regression value y = 0,081x-0,181 and R = 0,93 (p value 0,001). For the relationship between extract concentration and the log colony number of S. aureus, obtained regression value y = 2,250x- 1,521 and R2 = 0,72 (p value 0,001). In statistic test of E. coli, there was significant difference from six Averrhoa bilimbi L ethanolic concentration groups. Based on test Kruskal-Wallis analysis, p value was 0,003. In linearregression analysis, the relationship between extract concentration and the absorbance of E. coli bacteria, is generated with regression value y = 0,089x-0,212 and R = 0,89 (p value 0,001). For the elationship between extract concentration and the log colony number of E. coli, obtained regression value y = 0,526x + 6,998 value R2 = 0,79 (p value 0,001).Ethanolic extract of Averrhoa bilimbi L fruitwas effective against S. aureus and E. coli with MIC and MBC concentration of 1.56% (v/v). Increased concentration of Averrhoa bilimbi L ethanolic extract will increase the inhibition growth of S. aureus and E. coli bacteria Keywords : Averrhoa bilimbi L, belimbing wuluh, antibacterial, S. aureus, E. coli.